1997
DOI: 10.1002/(sici)1097-0142(19971115)80:10<1954::aid-cncr12>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of familial testicular cancer

Abstract: The current study underscores that susceptibility to testicular germ cell cancer is influenced by genetic factors. A family history of testicular cancer is encountered in about 1.35% of patients. The relative risk for first-degree relatives of patients with the disease is increased by a factor of 3-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 30 publications
1
12
0
2
Order By: Relevance
“…Previously reported data on age-at-diagnosis of familial TGCT are inconsistent; while some studies suggested that familial TGCT was diagnosed about 3 to 5 years earlier than sporadic cases [4, 11], which is similar to our findings, others did not show any differences [1214]. However, most of these studies were small series with limited numbers of familial cases.…”
Section: Discussionsupporting
confidence: 85%
“…Previously reported data on age-at-diagnosis of familial TGCT are inconsistent; while some studies suggested that familial TGCT was diagnosed about 3 to 5 years earlier than sporadic cases [4, 11], which is similar to our findings, others did not show any differences [1214]. However, most of these studies were small series with limited numbers of familial cases.…”
Section: Discussionsupporting
confidence: 85%
“…This historical information has recently been supplemented by a descriptive analysis of 461 kindred assembled by the ITCLC as part of its gene discovery activities (Mai et al 2009 b ). A meta-analysis indicates that an estimated 1.4% of men with newly diagnosed TGCT report a positive family history for this cancer (Dieckmann & Pichlmeier 1997). For the moment, suffice it to say that the case-report literature provides ample evidence to suggest that a hereditary form of TGCT might exist.…”
Section: Ftgcts: Does a Site-specific Genetic Syndrome Exist?mentioning
confidence: 99%
“…The age-standardized incidence rate worldwide is approximately 1.5/100,000, with substantial variations between countries [1]. Familial TGCT account for only a small number of all cases; approximately 1–3% of men with TGCT report one or more affected first-degree relatives [2, 3]. Family history is one of the few established risk factors for TGCT.…”
Section: Introductionmentioning
confidence: 99%